Evaluating optimum seeding distances from subsurface banding poultry litter in crop rotations. Issue 1 (30th January 2022) - Ashworth, A. J.; Nieman, C. C.
Abstract: Poultry litter is a nutrient‐dense fertilizer, but surface applications lead to nutrient losses to air, soil, and water. Objectives were to evaluate optimum subsurface‐applied poultry litter bands from crop seeding distance in a corn ( Zea Mays L.)–soybean [ Glycine max (L.) Merr.] rotation. Soil amendment treatments included planting 13, 25, and 38 cm from subsurface‐banded poultry litter, surface‐applied poultry litter, inorganic nitrogen (N), and 0 kg N ha −1 (control) in Year 1, followed by soybean in Year 2 (no new soil amendment applications). Across subsurface treatments, corn grain and silage yields were 45 and 30% greater compared with surface applications, respectively, with inorganic N not differing from 25‐ and 38‐cm bands during grain harvest. In Year 2, subsurface‐banded soybean grain yields were 26% greater than with inorganic N. Consequently, subsurface banding poultry litter may be an ecologically and agronomicallyviable replacement for surface litter applications in corn silage and grain systems and inorganic N in corn–soybean rotations. Core Ideas: Planting distance from poultry litter bands was evaluated for a corn–soybean rotation. Subsurface banding poultry litter allows for greater nutrient utilization. Subsurface corn grain and silage yields were greater than yields from surface applications. Subsurface banding litter >13 cm in a corn–soybean rotation may displace inorganic N.